2013
DOI: 10.1039/c3ra23337e
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation rate of Fe and electrochemical performance of Fe–air solid oxide rechargeable battery using LaGaO3 based oxide ion conductor

Abstract: Effects of oxidation rate of Fe powder in Fe-air solid oxide rechargeable battery on discharge potential and capacity were studied. From the measurement of P O 2 in Fe set chamber and AC impedance for electrode reaction, oxidation rate of Fe, i.e., formation rate of H 2 , was an important parameter for discharge performance of Fe-air solid oxide battery. Slow oxidation rate of Fe, namely, low current density, shows high discharge potential, however, caused sintering of Fe powder resulting in the decreased disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 18 publications
2
29
2
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18] Although the operating temperature, geometries and configurations for the flow battery systems reported in the literature vary to some degree, our multi-physics model presented here is developed for a close-loop tubular battery reactor working at 800…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18] Although the operating temperature, geometries and configurations for the flow battery systems reported in the literature vary to some degree, our multi-physics model presented here is developed for a close-loop tubular battery reactor working at 800…”
Section: Mathematical Modelmentioning
confidence: 99%
“…r 2 = −r 1 [17] where c 1 and c 2 are the molar concentrations of hydrogen and steam, and k and k −1 (in units of 1/s) are respectively the rate constants for the forward and reverse reactions. For species i, the volumetric mass source terms,R i , is the molar reaction rate scaled by the Molar mass, M i :…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first demonstration of oxide-ion-chemistry based anodesupported tubular Solid-Oxide Iron-Air Redox Battery (SOIARB) in 2011, 1 significant progress has been made experimentally in the areas of materials identification, 2-5 new metal-air chemistries 1,6-14 and performance optimization. [15][16][17][18][19][20] In contrast, theoretical understanding of the operating oxygen shuttle mechanisms of the new battery lags behind. In the open literature, only Ohmoti et al 21,22 and Guo et al 23 have reported multiphysics models for the battery.…”
mentioning
confidence: 99%
“…The advantages of SOMARB include double electron transfer (O 2− ), energy storage in a chemical bed separated from the electrode, fast charging and discharging rate, use of earth-abundant element such as iron for energy storage, scalability and operational safety. Since its debut in 2011, 1 significant progress has been made in the areas of electrochemical performance optimization, [2][3][4][5][6][7][8][9][10][11][12] new metal-air chemistries [13][14][15][16][17][18][19][20] and multiphysics modeling of electrochemistry, mass transport and chemical redox kinetics that govern the electrical behaviors of the battery. [21][22][23] However, these studies were all performed isothermally with a focus on evaluating the factors that can affect the electrochemical performance of the battery.…”
mentioning
confidence: 99%